OPTIMIZATION OF CASH FLOW MANAGEMENT DURING THE COVID-19 PANDEMIC IN THE HOME INDUSTRY OF THE FOOD AND CATERING BUSSINES IN TULUNGAGUNG REGENCY - MARLILA NUR'AINI; LANTIP SUSILOWATI (State Islamic Institute (IAIN) Tulungagung, 2021)
Covid-19 Pandemic that hit Indonesia had an impact on the national economy.. The purpose of this research is to find out how home industry efforts to manage its finances in order to maintain cash flow stability so that the company can survive and thrive amid the Covid-19 pandemic. The focus of the research was on the home industry and catering bussines in Tulungagung by taking four objects as sample, they are Home Industry dry food “SUIIP”, Home Industry wet food “Nisel Gallery”, catering bussines “Awaliyah Catering”, and Home Industry “Atastyfood Tulungagung”. The method used in this research is descriptive qualitative with data collection using interview techniques, observation, and documentation. Meanwhile, the analysis technique uses an inter-incentive approach. The results of this study show that the Covid-19 pandemic has had quite an impact on the home food industry and catering bussines in Tulungagung regency. Bussines management is carried out by maintaining the circulation of capita turnover, actively inovating products, and expanding market share with online media. With these efforts, the home industry of the food and catering bussines in Tulungagung regency can maintain productivity and maintain a stable cash flow.